Understanding the Goals and Tasks of Teaching Mathematics in Primary Grades (Eurasian Journal of Learning and Academic Teaching, 2023)
This article talks about the goals and tasks of the methodology of teaching mathematics in elementary grades and the use of modern pedagogical technologies